Attenuation of pathogenic Rift Valley fever virus strain through the chimeric S-segment encoding sandfly fever phlebovirus NSs or a dominant-negative PKR. Issue 8 (16th November 2016) - Nishiyama, Shoko; Slack, Olga A. L.; Lokugamage, Nandadeva; Hill, Terence E.; Juelich, Terry L.; Zhang, Lihong; Smith, Jennifer K.; Perez, David; Gong, Bin; Freiberg, Alexander N.; Ikegami, Tetsuro
ABSTRACT: Rift Valley fever is a mosquito-borne zoonotic disease affecting ruminants and humans. Rift Valley fever virus (RVFV: family Bunyaviridae, genus Phlebovirus ) causes abortions and fetal malformations in ruminants, and hemorrhagic fever, encephalitis, or retinitis in humans. The live-attenuated MP-12 vaccine is conditionally licensed for veterinary use in the US. However, this vaccine lacks a marker for the differentiation of vaccinated from infected animals (DIVA). NSs gene is dispensable for RVFV replication, and thus, rMP-12 strains lacking NSs gene is applicable to monitor vaccinated animals. However, the immunogenicity of MP-12 lacking NSs was not as high as parental MP-12. Thus, chimeric MP-12 strains encoding NSs from either Toscana virus (TOSV), sandfly fever Sicilian virus (SFSV) or Punta Toro virus Adames strain (PTA) were characterized previously. Although chimeric MP-12 strains are highly immunogenic, the attenuation through the S-segment remains unknown. Using pathogenic ZH501 strain, we aimed to demonstrate the attenuation of ZH501 strain through chimeric S-segment encoding either the NSs of TOSV, SFSV, PTA, or Punta Toro virus Balliet strain (PTB). In addition, we characterized rZH501 encoding a human dominant-negative PKR (PKRΔE7), which also enhances the immunogenicity of MP-12. Study done on mice revealed that attenuation of rZH501 occurred through the S-segment encoding either PKRΔE7 or SFSV NSs. However, rZH501 encoding either TOSV, PTA, or PTB NSs in the S-segment uniformly caused lethal encephalitis. Our results indicated that the S-segments encoding PKRΔE7 or SFSV NSs are attenuated and thus applicable toward next generation MP-12 vaccine candidates that encode a DIVA marker.